Correction: High iodine adsorption performances under off-gas conditions by bismuth-modified ZnAl-LDH layered double hydroxide. Issue 57 (16th September 2020) - Dinh, Trinh Dinh; Zhang, Dongxiang; Tuan, Vu Ngoc
Abstract : Correction for 'High iodine adsorption performances under off-gas conditions by bismuth-modified ZnAl-LDH layered double hydroxide' by Trinh Dinh Dinh et al., RSC Adv., 2020, 10, 14360–14367, DOI: ; 10.1039/D0RA00501K .